2015
DOI: 10.1016/j.amjmed.2014.07.042
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary Care Program for Advanced Chronic Kidney Disease: Reduces Renal Replacement and Medical Costs

Abstract: Our analysis demonstrated that the multidisciplinary care program provided better health care and reduced renal replacement therapy in patients with advanced chronic kidney disease. By decreasing hospitalizations, emergent start, and the need for renal replacement therapy, the multidisciplinary care program was cost-effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
88
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(94 citation statements)
references
References 20 publications
4
88
0
1
Order By: Relevance
“…Full-text of 44 articles was obtained for the analysis and 25 articles were excluded because the number of patients who died or commenced dialysis were not reported (n = 21, including 8 studies in Chinese), the composition of MDC team was not shown (n = 3), and a study from the same group of patients (n = 1) [14,18]. The final analysis conducted was based on 8853 patients of 18 studies with a mean age of 63 ± 12 years old [9][10][11][12][13][14][15][18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: Literature Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…Full-text of 44 articles was obtained for the analysis and 25 articles were excluded because the number of patients who died or commenced dialysis were not reported (n = 21, including 8 studies in Chinese), the composition of MDC team was not shown (n = 3), and a study from the same group of patients (n = 1) [14,18]. The final analysis conducted was based on 8853 patients of 18 studies with a mean age of 63 ± 12 years old [9][10][11][12][13][14][15][18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: Literature Searchmentioning
confidence: 99%
“…MDC had also been used in patients with CKD but the beneficial effects of MDC on CKD patients' clinical outcomes were controversial in the published studies. MDC was associated with lower all-cause mortality [9][10][11] and lower risk of dialysis [10,12] in some but not all studies [13][14][15].…”
Section: Introductionmentioning
confidence: 97%
“…The present study did not find notable benefits of adopting multidisciplinary pre-dialysis care approach on outcomes, as had been shown in several other reports in the same country [32,33,34]. The reason for such a discrepancy was not clear but could be related in part to varied study designs and patient populations.…”
Section: Discussionmentioning
confidence: 35%
“…Several comorbidities of the EuroSCORE models are chronic diseases with well-known effects on a patient's life expectancy that are not removed with surgery [5], and Figure 4 shows that most of the associated diseases defined in the EuroSCORE II model also affect long-term survival. Chronic kidney failure and the need for dialysis are associated with higher rates of rehospitalization and death even for nonsurgical populations; and also chronic obstructive pulmonary disease, extracardiac arteriopathies, and diabetes mellitus are some of those diseases that affect long-term life expectancy and increase health costs [16][17][18]. Chronic heart failure at the time of surgery is expected to affect the outcomes beyond the immediate surgical results, as clearly demonstrated by poor outcomes of patients with compromised cardiac function [19].…”
Section: Commentmentioning
confidence: 99%